Does poor spousal health negatively affect own health among elderly retired Japanese couples? A 1-year follow-up study - Yoko Muramatsu; Kuniyasu Takagi; Tomoko Suzuki; Bibha Dhungel; Akihiro Tsuchiya; Koji Wada (Elsevier, 2021)
Background: We aimed to determine whether poor spousal health affected respondents' own self-rated health after 1 year among older retired Japanese couples. Methods: Data were extracted from the nationwide population-based survey, the "Longitudinal Survey of Middle-aged and Elderly Persons", which has been conducted annually since 2005 by the Japanese Ministry of Health, Labour and Welfare. We used 2016 survey data as a baseline and 2017 data for 1-year follow-up. Baseline respondents comprised 21,916 individuals; of these, we focused on 4397 respondents who were retired, married, aged 65-70 years, and had good self-rated health. The survey included questions about respondents' own health and lifestyle, and their spouses' health status. Multivariate logistic regression analysis was used to explore the association between spousal health at baseline and respondents' own self-rated health after 1 year. Results: We found that poor spousal health is associated with respondents' own self-rated poor health after 1 year. The odds ratio (OR) for worsening health was 1.67 (95% confidence interval (CI): 1.11-2.52) for men and 1.72 (95% CI: 1.25-2.37) for women when their spouse's health was "somewhat bad". The OR was 2.25 (95% CI: 1.40-3.62) for women when spousal health was "bad/very bad", compared with "somewhat good". Conversely, good spousal health was associated with a low risk of declining health for respondents after 1 year. The association for men was apparent when their spouse's health was "good" [OR: 0.69; 95% CI: 0.49-0.98], and the association for women was apparent when their spouse's health was "very good" [OR: 0.46; 95% CI: 0.24-0.90]. Conclusions: Poor spousal health is an independent factor that negatively affects own self-rated health after 1 year among retired couples in Japan aged 65-70 years.